Electrochemical reduction of carbon dioxide : overcoming the limitations of photosynthesis - Marken, Frank; Fermin, David (RSC energy and environment series ;, 2018)
Providing a comprehensive overview, this book is ideal for researchers and industrial chemists working in environmental science, electrochemistry and chemical engineering.